تطبيقات الحوسبة السحابية في دعم مهارات البحث العلمي وحفظ واسترجاع المعلومات لدى طالبات قسم علم المكتبات والمعلومات: دراسة حالة - الهيف, عاليه (مجلة (اعلم), 2024)
هدفت الدراسة إلى قياس فاعلية استخدام تطبيقات الحوسبة السحابية لدى طالبات قسم المكتبات والمعلومات بجامعة الأميرة نورة بنت عبد الرحمن على تنمية وزيادة مهارات البحث العلمي، بما يشمل التخزين السحابي للملفات والوصول الدائم للمعلومات لجميع الطالبات مع القدرة على الاستخدام وإنشاء الملفات ورفعها وتحميلها وتعديلها، وذلك من خلال مستندات جوجل وقواعد البيانات وجداول البيانات . استخدمت الدراسة كل من المنهجين المسحي الميداني والوصفي التحليلي لتحقيق أهداف الدراسة وتساؤلاتها، مستعينة بأداة الدراسة الرئيسة (الاستبانة) وقد شملت عينة الدراسة عدد(151) من طالبات قسم المكتبات والمعلومات ، وقد تم الاختيار عشوائي خلال الفصل الدراسي الثالث عام 1444 وقد توصلت الدراسة الى وجود وعي الطالبات بأهمية استخدام تطبيقات الحوسبة السحابية في المهام البحثية حيث ان اكثر من نصف العينة يستخدمونها بشكل دائم . إضافة ان من المصادر الأساسية لمعلومات الطالبات عن الحوسبة هي التعلم الذاتي بحوالي 69% . وقد كان من أهم توصيات الدراسة ضرورة امتلاك الطالبات المهارات الكافية لاستخدام تطبيقات الحوسبة السحابية وتفعيلها في أثراء البحوث العلمية كما وكيفا . إضافة الى التأكيد على توفر البنية التحتية والتي تتوافق مع خدمات الحوسبة الالكترونية الحديثة . Abstract The study aimed to measure the effectiveness of using cloud computing applications among female students of the Library and Information Department at Princess Noura bint Abdul Rahman University to develop and increase scientific research skills, including cloud storage of files and permanent access to information for all students with the ability to use, create, upload, download and modify files, through... Google Docs, databases, and spreadsheets. The study has been used two approaches Case study and descriptive analytics to achieve the objectives and questions of the study, using the main study tool (the questionnaire). The study sample included a few (151) female students from the Library and Information Department. Random selection was made during the third semester in the year 1444. The study concluded that there was Female students’ awareness of the importance of using cloud computing applications in research tasks, as more than half of the sample uses them permanently. In addition, about 69% of the primary sources of female students’ information about computing is self-learning. One of the most important recommendations of the study was the need for female students to have sufficient skills to use cloud computing applications and activate them to enrich scientific research qualitatively and quantitatively. In addition to emphasizing the availability of infrastructure that is compatible with modern electronic computing services.